Lactobacillus paracasei CNCM I-5220-derived postbiotic protects from the leaky-gut - Algieri, Francesca; Tanaskovic, Nina; Rincon, Cindy Cardenas; Notario, Elisabetta; Braga, Daniele; Pesole, Graziano; Rusconi, Roberto; Penna, Giuseppe; Rescigno, Maria (Frontiers in Microbiology, 2023)
The maintenance of intestinal barrier function is essential for preventing different pathologies, such as the leaky gut syndrome (LGS), which is characterized by the passage of harmful agents, like bacteria, toxins, and viruses, into the bloodstream. Intestinal barrier integrity is controlled by several players, including the gut microbiota. Various molecules, called postbiotics, are released during the natural metabolic activity of the microbiota. Postbiotics can regulate host-microbe interactions, epithelial homeostasis and have overall benefits for our health. In this work, we used in vitro and in vivo systems to demonstrate the role of Lactobacillus paracasei CNCM I-5220-derived postbiotic (LP-PBF) in preserving intestinal barrier integrity. We demonstrated in vitro that LP-PBF restored the morphology of tight junctions (TJs) that were altered upon Salmonella typhimurium exposure. In vivo, LP-PBF protected the gut vascular barrier and blocked S. typhimurium dissemination into the bloodstream. Interestingly, we found that LP-PBF interacts not only with the host cells, but also directly with S. typhimurium blocking its biofilm formation, partially due to the presence of biosurfactants. This study highlights that LP-PBF is beneficial in maintaining gut homeostasis due to the synergistic effect of its different components. These results suggest that LP-PBF could be utilized in managing several pathologies displaying an impaired intestinal barrier function.